Assessing Safety Training and Workers’ Participation that Affect Safety Performance in Eversendai Corporation Berhad - Hafiz, Muhd Ilham Hafizy; Mohd Adi, Mohd Nazir (Research in Management of Technology and Business, 2023)
Safety and health training is essential for organizational safety and health management because it enhances workers’ understanding of safety and health challenges in organizations and raises their awareness of workplace dangers, thereby reducing accidents and boosting workers’ productivity. This study aims to measure the level of safety training and workers’ participation and the relationship between workers’ participation and safety training with safety performance in manufacturing sectors in Eversendai Corporation Berhad Selangor, Malaysia. This study employed quantitative research methods, including questionnaires to collect quantitative data. An online survey was conducted among 217 manufacturing workers at Eversendai Corporation Berhad in Selangor. Data were evaluated by using reliability analysis, descriptive analysis, and Spearman’s correlation analysis. The study finds that there is a positive relationship between safety training and worker’s participation with safety performance at Eversendai Corporation Berhad.